2010
DOI: 10.5120/139-257
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of various levels of Fusion of Multi-focused Images using Wavelet Transform

Abstract: The fast development of digital image processing leads to the growth of feature extraction of images which leads to the development of Image fusion. Image fusion is defined as the process of combining two or more different images into a new single image retaining important features from each image with extended information content. There are two approaches to image fusion, namely Spatial Fusion and Transform fusion. In Spatial fusion, the pixel values from the source images are directly summed up and taken ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…The iris pattern was encoded by Gabor filters after the process of segmentation and normalization. Kannan et al [3] evaluated the performance of all levels of multifocused image fusion using Discrete Wavelet Transform, Stationary Wavelet Transform, Lifting Wavelet Transform, Multi Wavelet Transform, Dual Tree Discrete Wavelet Transform and Dual Tree Complex Wavelet transform in terms of various performance measures. Shah et al [4] presented a novel fusion rule which can efficiently fuse multifocus images in the wavelet domain by taking a weighted average of the pixels.…”
Section: Related Workmentioning
confidence: 99%
“…The iris pattern was encoded by Gabor filters after the process of segmentation and normalization. Kannan et al [3] evaluated the performance of all levels of multifocused image fusion using Discrete Wavelet Transform, Stationary Wavelet Transform, Lifting Wavelet Transform, Multi Wavelet Transform, Dual Tree Discrete Wavelet Transform and Dual Tree Complex Wavelet transform in terms of various performance measures. Shah et al [4] presented a novel fusion rule which can efficiently fuse multifocus images in the wavelet domain by taking a weighted average of the pixels.…”
Section: Related Workmentioning
confidence: 99%
“…Stationary wavelet transform (SWT) [1] is modified DWT where this drawback is removed by removing the down samplers and up samplers in DWT and up sampling the filter coefficients by a factor of 2(j-1)in the jth level of the algorithm. Borwonwatanadelok et al [32] , Somkait et al [33] and kannan et al [34] have shown that This method provides good result at level 2 of decomposition but it is very time consuming.…”
Section: Stationary Wavelet Transform (Swt) Based Image Fusionmentioning
confidence: 99%
“…Stationary Wavelet Transform(SWT) [32][33][34] This method provides good result at level2 of decomposition It is time consuming…”
Section: International Journal Of Computer Applications (0975 -8887)mentioning
confidence: 99%
“…A. Toet proposed an algorithm for image fusion by a ratio of low pass pyramid [5]. K. Kannan et al evaluated the performance of all the levels of multi-focused images using different wavelet transforms [6]. Dong et al discussed various advances in multi-sensor data fusion [7].…”
Section: Introductionmentioning
confidence: 99%